Donald Trump, the Christian Right and COVID-19: The Politics of Religious Freedom - Jeffrey Haynes (Laws, 2021)
This paper examines the issue of religious freedom in the USA during the coronavirus pandemic of 2020–2021, during the presidency of Donald Trump (2017–2021). It contends that the ability of state governors to close religious places of worship illustrates both the limits on the power of the president and that public health can take supremacy over religious freedom in today’s America. The paper is organised as follows: first, we identify the importance of religious freedom for the more than 20 million Americans who self-classify as Christian evangelicals. Second, we assess the transactional importance that President Trump placed on Christian evangelicals’ religious freedom. Third, we look at one kind of Christian evangelicals—that is, Christian nationalists—to see how they regarded restrictions on their religious behaviour caused by COVID-19. Fourth, we briefly examine several recent legal cases brought against the governors of California and Illinois by the Liberty Counsel, the leading Christian evangelical legal firm in the USA. Led by Matthew Staver, Dean of the Liberty University Law School, Liberty Counsel regularly represents Christian nationalists who challenge state-imposed restrictions on religious gatherings during the coronavirus pandemic.